Enhancing Customer Interaction with Chatbot in Digital Marketing for Traditional Balinese Food Sellers - Anak Agung, Sandatya Widhiyanti; I Gusti Agung Ayu Sekarini (PT ARRUS Intelektual Indonesia, 2024)
This research explores the potential of chatbot to enhance interactions between consumers and traditional Balinese food sellers. Besides that, this research promotes Balinese specialties, improves customer experience, and supports local tourism by increasing accessibility to information. Research methods include literature review, surveys, data collection, prototype development, implementation, and result analysis. The Bakul BOT application was developed, and testing involved Black Box Testing for functionality and the System Usability Scale (SUS) for user satisfaction. Test results showed all features worked as expected, with an average SUS score of 83, placing Bakul BOT in grade A, categorized as